Understanding the biomechanical influence of core contribution in squat: A systematic review - Shu, H.; Yang, X.; Wang, Y.; Fernandez, J.; Mei, Q.; Gu, Y. (Isokinetics and Exercise Science, 2025)
Background Squat exercises have been widely employed in fitness, rehabilitation, sports performance, and strength training under either free weight or weight-bearing conditions.